An analysis of procedures that affect response variability. Issue 3 (17th May 2017) - Dracobly, Joseph D.; Dozier, Claudia L.; Briggs, Adam M.; Juanico, Jessica F.
Abstract : Response variability is sensitive to antecedent and consequent manipulations. Researchers have investigated inducement, direct production through reinforcement, and stimulus control of response variability. Recently, researchers have shown that lag reinforcement schedules reliably increase variability but may also produce higher‐order stereotypy. There has been limited investigation of appropriate variability levels and alternation between repetition and variation. In a three‐part study, we evaluated levels of variability across a group of children, the effects of various procedures on producing response variability and novelty, and the use of schedule‐correlated stimuli for producing rapid alternation between repetition and variation. In Study 1, there was a nearly bimodal distribution of children emitting either low or high variability. In Study 2, for most children, fixed lag 4 and variable lag 4 schedules produced the highest levels of variability and novelty. In Study 3, responding was brought under control of schedule‐correlated stimuli, allowing for rapid alternation between repetition and variation.